2019
DOI: 10.1186/s12998-018-0226-7
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation-induced hypoalgesia in musculoskeletal pain populations: a systematic critical review and meta-analysis

Abstract: BackgroundManipulation-induced hypoalgesia (MIH) represents reduced pain sensitivity following joint manipulation, and has been documented in various populations. It is unknown, however, whether MIH following high-velocity low-amplitude spinal manipulative therapy is a specific and clinically relevant treatment effect.MethodsThis systematic critical review with meta-analysis investigated changes in quantitative sensory testing measures following high-velocity low-amplitude spinal manipulative therapy in muscul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(52 citation statements)
references
References 44 publications
2
47
2
1
Order By: Relevance
“…These results are strengthened by similar findings in the literature but on study subjects with musculoskeletal problems. Thus a recent systematic review concluded that there was no effect of SM on the pressure pain threshold in people with musculoskeletal problems [18] A recent subsequent study, using the same sham as us with verification of blinding afterwards, also failed to identify an effect of SM on PPT in people with musculoskeletal problems [19].…”
Section: Comparison With Literaturementioning
confidence: 90%
See 1 more Smart Citation
“…These results are strengthened by similar findings in the literature but on study subjects with musculoskeletal problems. Thus a recent systematic review concluded that there was no effect of SM on the pressure pain threshold in people with musculoskeletal problems [18] A recent subsequent study, using the same sham as us with verification of blinding afterwards, also failed to identify an effect of SM on PPT in people with musculoskeletal problems [19].…”
Section: Comparison With Literaturementioning
confidence: 90%
“…Sample size calculation was performed using a repeated measures approach. We found that we would need 43 subjects in each group to show at least a difference of 15% of change between groups ('supposed' percentage of clinical significance [18]), with the mean pressure pain threshold of 500 kg/cm2 at baseline. However, as this minimum clinical difference of the PPT is not clearly defined [18], the basis for this power calculation was purely speculative.…”
Section: Statistical Analysis Preliminary Analysesmentioning
confidence: 99%
“…Pain sensitivity. The literature concerning the hypoalgesic effect of SMT is conflicting [15][16][17] . This may be the result of differences in study populations as they often are heterogeneous, and includes asymptomatics participants 17 as well as participants with musculoskeletal conditions often found in the general public or primary care 16 .…”
Section: Patient Reported Low Back Pain Intensity Whether the Reductmentioning
confidence: 99%
“…Recent systematic reviews have observed that there might be differences in manipulation-induced hypoalgesia based on where the SMT is applied [29,50]. Since studies often show no change in PPT after lumbar SMT in clinical populations [29], it may be that the question of whether a participant's pain trajectory acts as a modifier of manipulation-induced hypoalgesia is irrelevant in this population (at least regarding PPT). This topic may be worth pursuing in other regions of the spine.…”
Section: Explanation and Comparisonsmentioning
confidence: 99%
“…It has also been suggested that changes in QST outcomes after manual therapy interventions, such as spinal manipulative therapy (SMT) and mobilisation, may help explain the positive clinical outcomes for musculoskeletal pain seen in some patients [28]. Short-term increases in PPT and attenuation of TS have been observed following SMT and mobilisation in people with musculoskeletal pain [29,30]. Since there are differences in pain processing and QST outcomes between asymptomatic and chronic LBP patients, and potentially between different LBP trajectories, it is also possible that changes in QST measures after an intervention may differ between LBP trajectories.…”
Section: Introductionmentioning
confidence: 99%